Brain MRI in patients with diffuse psychiatric/neuropsychological syndromes in systemic lupus erythematosus. Issue 1 (3rd November 2014) - Arinuma, Yoshiyuki; Kikuchi, Hirotoshi; Wada, Tatsuhiko; Nagai, Tatsuo; Tanaka, Sumiaki; Oba, Hiroshi; Hirohata, Shunsei
Abstract : Background: Manifestations in neuropsychiatric systemic lupus erythematosus (NPSLE), especially active diffuse NPSLE syndromes, are some of the most difficult complications of the disease. For the evaluation and the diagnosis of central nervous system manifestations, including NPSLE, MRI is a very useful tool to detect the various abnormalities. However, the relationship between brain MRI findings and clinical variables has not yet been clarified in patients with diffuse NPSLE. Objectives: The aim of this study is to investigate the pathogenesis of diffuse NPSLE, by comparing various parameters such as serum autoantibodies and cytokines in cerebrospinal fluid (CSF) with abnormal findings revealed on brain MRIs in patients with diffuse NPSLE. Methods: Fifty-three patients with diffuse NPSLE admitted to our University Hospital from 1992 to 2012 were exhaustively enrolled in this study. Their medical charts and brain MRI scans were reviewed. The relationship of MRI abnormalities with various parameters was analysed. Results: As many as 25 of 53 patients (47.2%) had abnormal MRI findings. MRI findings improved after treatment in 10 of 17 patients for whom follow-up studies were available. MRI abnormalities were not correlated with age at the onset of diffuse NPSLE. However, the disease duration of SLE was significantly longer in patients with abnormal MRI findings (p=0.0009). MRI abnormalities were not significantly associated with serum autoantibodies. However, there were significant elevations of the CSF protein level (p=0.0106) and the CSF interleukin 6 level (p=0.0225) in patients with abnormal MRI findings. Patients with MRI abnormalities showed significantly higher overall mortality (p=0.0348). Conclusions: The results revealed that MRI abnormalities in diffuse NPSLE might be heterogeneous with regard to their reversibility. These data also indicate that patients with diffuse NPSLE and MRI abnormalities have more severe inflammation in the central nervous system related to the activity of diffuse NPSLE, as evidenced by poorer prognosis.